"Krąg biblijny" Romana Brandstaettera jako autobiografia duchowa = "The Biblical circle" by Roman Brandstaetter as his spiritual biography - Bednarczyk-Stefaniak, Emanuela; Seul, Anastazja (1961- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article "The Biblical circle by Roman Brandstaetter as his spiritual biography" carries out an analysis of "The Biblical circle" angling toward autobiographical content. It is focusing on two aspects of the inner world of the writer himself: intellectual content (testimonials of books he read)and spiritual content (personal experience of his time with God).
Keywords: Brandstaetter, Roman (1906-1987); Biblia; autobiografia duchowa; mistyka; doświadczenie wiary; Bible; spiritual autobiography; mysticism; faith experience